Association of APOE genotype and lipid lowering with cognitive function in a randomized placebo‐controlled trial of Evolocumab: Developing topics. (7th December 2020) - Korthauer, Laura E; Giugliano, Robert; Guo, Jianping; Sabatine, Marc; Sever, Peter; Keech, Anthony; Pedersen, Terje; Kurtz, Christopher; Ruff, Christian; Mach, Francois; Ott, Brian R
Abstract: Background: APOE encodes a cholesterol transporter, and the ε4 allele is associated with higher cholesterol levels, ß‐amyloid burden, and risk of Alzheimer's disease (AD). A recent pooled re‐analysis of clinical trials (Geifman et al., 2017) found that long‐term use of cholesterol‐lowering medications may lower rates of cognitive decline in patients with mild to moderate AD, with potentially greater therapeutic efficacy for ε4/ε4 carriers. Prior studies demonstrated no significant differences in objective or subjective cognitive function for patients receiving the PCSK9 inhibitor evolocumab vs. placebo added to statin therapy. The purpose of this study was to determine whether APOE genotype moderates the relationships between evolocumab, LDL cholesterol level, and cognitive function. Method: Of 16, 174 APOE‐genotyped patients (25.8% with one ε4 allele; 2.3% with two ε4 alleles) from FOURIER, a randomized, placebo‐controlled trial of evolocumab added to statin therapy, 13, 481 completed the Everyday Cognition Scale (ECog) to report subjective cognitive changes from the end of the trial compared to its beginning (scores ≥2 reflect subjective decline). A subset (N = 835) underwent objective cognitive testing using the Cambridge Neuropsychological Test Automated Battery as part of the EBBINGHAUS trial. Result: There was a dose‐dependent relationship between APOE ε4 genotype and subjective memory decline on the ECog in the placebo arm ( p = .009; ε4/ε4 carriers vs. non‐carriers: OR = 1.38, 95% CI [.98, 1.95]) but not the evolocumab arm ( p = .77, OR = 1.14, 95% CI [.81, 1.60]). However, the genotype x treatment interactions were not significant, likely due to a limited number of ε4/ε4 carriers. After adjustment for demographic and medical covariates, APOE genotype did not significantly moderate the relationships between treatment arm or post‐baseline LDL cholesterol level on CANTAB performance ( p 's>.05) in the subset examined. Conclusion: APOE genotype did not significantly moderate the relationship between evolocumab treatment and cognitive function, although analyses were limited by the low population frequency of the ε4/ε4 genotype. This supports the cognitive safety of evolocumab among ε4 carriers, guiding future research on possible benefits of cholesterol‐lowering medications in people at genetic risk for Alzheimer's disease.